Consequence of Farmer’s Attributes on their Attitude towards Bt-Cotton - M .K.Trivedi; N.B.Chauhan; Umesh Chinchmalatpure (Journal of Agricultural Extension Management, 2025)
Cotton is one of the most important commercial crops playing a key role in economic, political and social affairs of the world. Due to its importance in agricultural as well as industrial economy, it is also called "white gold". Cotton is cultivated in about 60 countries in the world and India ranks first in area and production in the world, albeit with low productivity. Bt Cotton is an important biotechnological intervention that has become controversial because of its implications for risk, safety, sustainable development and ethical issues (Karthikeyan, 2007). The use of Bt cotton is a positive step towards environmental protection because it makes possible the reduction of insecticide load in the environment and reduces the handling of such chemicals by farmers. On the other hand genetical contamination, health impacts and compatibility to the Indian environment are the most common arguments among the biodiversity experts against Bt technology. In this regard the consequences perceived by the cotton growers due to adoption of Bt. cotton are a very crucial aspect.